Estudo in vitro do composto lead PTC+ em modelo de câncer de próstata metastático: aplicações do High Content Imaging (HCI), e desenvolvimento de nanoformulações lipossomais vetorizadas com o anticorpo anti-EGFR - Vieira Neto, José de Brito (2023)
Prostate cancer affects thousands of patients in Brazil and has high mortality rates, representing it a serious public health problem. In this context, current therapy has limited efficacy, therefore there is a need to develop new drugs and delivery strategies for molecules in use and for new molecules. Thus, the emergence of new compounds such as (+)-(6aS,11aS)-2,3,9-trimetoxypteroarpan (PTC+) may provide a new horizon in cancer treatment since it shows antitumor activity in various cancers via inhibition of mitotic spindle formation. In addition, the development of nanostructured drug release systems is advantageous, allowing by-pass, by improving solubility and pharmacokinetics, as well as by increasing the stability of the encapsulated drug, allowing slow and sustained release, thus reducing the need for frequent administrations, and targeting solid tumors through the EPR effect. In addition, the functionalization of nanocarriers, for example liposomes, with monoclonal antibodies, such as the anti-EGFR antibody, which has the potential to recognize the EGF receptor overexpressed in some types of prostate cancer, allows targeted and specific release into the tumour cell, aim to reduce the drug's side effects. The aim of this study was to carry out an in vitro phenotypic analysis of the new antitumor drug PTC+ using the High Content Imaging technique. In addition, the development of liposomes and anti- EGFR immunoliposomes encapsulated with PTC+. Moreover, this study focuses on the development of protype biosimilar anti-EGFR antibody, covering the stages of genetic construction, expression and characterization. The results show that the lead compound PTC+ inhibits the formation of the mitotic spindle in the DU145 and LNCaP cell lines. In addition, PTC+ promotes disorganization in the microtubules of interphase cells. The biosimilar antibody showed a similar structural profile to the reference antibody, as well as being able to bind to EGFR in a similar way to the reference. Regarding the nanoformulations, the liposomes showed a high encapsulation efficiency of 90% accompanied by satisfactory physicochemical parameters, such as a size of 90nm and a PDI index of 0.2. The immunoliposomes were functionalized with a satisfactory efficiency of 48% with cetuximab. Furthermore, immunoliposomes promoted better cellular uptake and improved the cytotoxicity in DU145 cells when compared to liposomes. Hence, the PTC+ compound possibly exerts its anti-tumour effect via depolymerization of the microtubules and inhibition bipolar spindle formation. In addition, the nanoformulations developed in this work showed antitumor potential in vitro, allowing prospects for their use in vivo. Besides that, the prototype biosimilar showed similar structural and functional patterns to the reference one.